Soil test crop response studies on potato (Solanum tuberosum L.) in acid inceptisols of Meghalaya - Muddana Sri Sai Charan Satya; Swami, Sanjay (Umiam : CPGSAS, CAU-Imphal, 2023)
Three field experiments were conducted in College of Post Graduate Studies in Agricultural Sciences, Central Agricultural University, Umiam, Ri-bhoi district, Meghalaya during kharif and rabi season of 2021-22 and 2022-23 to work out the soil test crop response based fertilizer requirement in combination with FYM for targeted yield of potato (Solanum tuberosum L.). Prior to test crop experiment, a field experiment to stabilize the soil fertility was conducted during kharif 2021 by dividing the experimental field into four equal strips and applying graded doses of fertilizer nutrients. An exhaust crop i.e., maize (Zea mays L.) was grown to create soil fertility gradient artificially. Test crop potato was grown during rabi 2021-22, after dividing each strip in 28 plots (24 treatments + 4 controls). Potato response to selected combinations of four levels of organics (0, 5, 10, 15 t ha-1), four levels of nitrogen (0, 60, 120, 180 kg ha-1), four levels of phosphorus (0, 60, 120, 180 kg ha-1), four levels of potassium (0, 30, 60, 90 kg ha-1) in strips of varied fertility was studied. The values of soil available nitrogen, phosphorus and potassium ranged between 269.80 to 311.23 kg ha-1, 9.84 to 21.28 kg ha-1 and 217.69 to 261.04 kg ha-1, respectively before the test crop experiment on potato. Tuber yield of potato varied from 5182 to 16046 kg ha-1. Total uptake of N, P and K by potato ranged from 20.13 to 112.03 kg N ha-1, 3.80 to 24.30 kg P ha-1 and 34.38 to 146.14 kg K ha-1. Nutrient requirement to produce one quintal of potato tuber was 0.55 kg N, 0.26 kg P2O5 and 0.93 kg K2O. Per cent contribution of N, P and K from soil was 8.30, 46.21 and 17.74, respectively. Likewise, per cent contribution of N, P and K from FYM was 11.33, 7.10 and 10.35, respectively, whereas percent contribution of N, P and K from fertilizer was 33.32, 15.72 and 91.46, respectively. Fertilizer nutrient prescription equations for targeted yield of potato were developed without FYM and with FYM and it was found that a particular yield target for fertilizer nutrient requirement decreased with increasing soil test values. Application of FYM reduced the fertilizer nutrient requirement for the crop. The fertilizer adjustment equations evolved during previous season for the potato was tested during rabi 2022-23 with eleven treatments in randomized complete block design with three replications. Results revealed that application of fertilizer nutrients as per targeted yield equation with yield target of 150 q ha-1 with IPNS was found superior in terms of plant height (cm), number and weight of tubers per plant (gm), tuber yield (t ha-1), haulm yield (t ha-1), N, P and K content (%) and uptake (kg ha- 1) and soil available nutrients (kg ha-1). Whereas, STCR-IPNS was found to be at par with STCR-NPK with targeted yields 100, 125 and 150 q ha-1. Application of fertilizers as per yield target 150 q ha-1 has recorded significantly highest tuber yield (15.46 t ha- 1), haulm yield as (5.15 t ha-1), uptake of nitrogen (168.35 kg ha-1), phosphorus (34.88 kg ha-1), potassium (201.79 kg ha-1). The available nutrient status of nitrogen (300.13 k ha-1), phosphorus (23.12 kg ha-1), potassium (267.63 kg ha-1) was recorded with application of chemical fertilizers (150 q ha-1 targeted yield). Based on STCR experimentation, it can be concluded that the potato yield target 125 q ha-1 and 150 q ha-1 was achieved by using soil test based fertilizer prescription equation and maintaining the soil fertility. It indicated the validity of targeted yield equation for potato in acid Inceptisol of Ri-bhoi district of Meghalaya.
Includes bibliographical references.